PENTINGNYA MELINDUNGI KULIT DARI SINAR ULTRAVIOLET DANCARA MELINDUNGIKULIT DENGAN SUNBLOCK BUATAN SENDIRI - Siti Hapsah Isfardiyana (Asian Journal of Innovation and Entrepreneurship, 2014)
Ultra violet rays useful for human beings is such as to synthesize Vitamin D andalso serves to kill bacteria. But besides the benefits ultra violet rays can harm humans ifexposed tohuman skin for too long. Some of the negative effects caused by exposure toultraviolet light too long is redness of the skin, a skin burn, until it can lead to skincancer. The skin has a natural protection system that is a layer of melanin. However, it isnot enough to protect the skin from harmful ultraviolet rays. One way to protect skin isto use sunblock. Dusun KarangBulu dan KarangPandan located in the village KenaibanJuwiring District of Klaten district. Klaten Regency climatic conditions including atropical climate with a wet season and a dry seasonalternatedhroughout the year, theaverage air temperature 28-30 degrees.Dusun Karang Bulu dan Karang Pandan , it isnecessary to protect the skin from sun exposure, moreover, most of the residentsworkas farmers where most of the time spent outdoors. Therefore, people need to knowhow to make a sunblock that is affordable to the public. Residents are very excitedabout the information that is shared, but some residents were unable to attend becausethere busyness.